“Análisis de la evaluación de desempeño docente del nivel de grado de la Unidad de Educación a Distancia y en Línea (UEDL) de la Universidad Nacional de Loja (UNL) periodo octubre 2022- marzo 2023” - Mena V·squez, Blanca Paulina (2024)
The research work "Analysis of the evaluation of teaching performance at the undergraduate level of the Distance and Online Education Unit (UEDL) of the National University of Loja (UNL) period October 2022 - March 2023", aims to analyze the evaluation of teaching performance and propose strategies to improve the efficiency of undergraduate teachers of the Distance and Online Education Unit of the National University of Loja, evaluate the criteria and methodology used in the evaluation of teaching performance of the Distance and Online Education Unit of the National University of Loja, and propose an improvement plan based on the results obtained from the analysis of the evaluation. The type of research is descriptive and correlational since it seeks to describe and analyze the application of management and leadership skills and their correlation with teaching performance in the UEDL. Its methodological approach is mixed, therefore it combines quantitative and qualitative methods. The results obtained allow us to conclude that the methodological process used in the evaluation of teachers' performance is adequate and participatory; in which students, teachers, academic peers and directors of each program participate. This process is regulated by university regulations; in the same way, the evaluation contributed to the improvement of the academic quality of each program through the execution of improvement plans created in relation to the results of the evaluation carried out; finally, it is suggested that the directors of the program of the UEDL carry out a permanent follow-up regarding the fulfillment of the improvement plans proposed based on the evaluation carried out.